2014
DOI: 10.1007/s10965-014-0600-7
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification of TiO2 nanoparticles with 1,3,5-triazine based silane coupling agent and its cumulative effect on the properties of polyurethane composite coating

Abstract: The present work focuses on the development of functional polyurethane hybrids through the incorporation of surface modified TiO 2 nanoparticles. For improving the nanoparticle dispersion and increasing possible interactions between nano-particles and polyurethane matrix, the surface of the nano-particles was modified with 1,3,5-triazine core silane coupling agent. The surface modification of nanoparticles was confirmed by FESEM, FT-IR and Raman spectroscopic techniques. The functionalized nanoparticles were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Photoactivity of TiO 2 , according to its application, can be reduced or increased through coupling [4], dye sensitization [2,5], and surface modification [6][7][8][9][10][11][12] and also doping metals, nonmetals or ionic compounds into the crystal structure [13,14] of the TiO 2 . In coatings industry, improve the properties and/or develop functional coatings via incorporation the nanoparticles such as TiO 2 nanoparticles have received many attractions, both in industry and in academia.…”
Section: Introductionmentioning
confidence: 99%
“…Photoactivity of TiO 2 , according to its application, can be reduced or increased through coupling [4], dye sensitization [2,5], and surface modification [6][7][8][9][10][11][12] and also doping metals, nonmetals or ionic compounds into the crystal structure [13,14] of the TiO 2 . In coatings industry, improve the properties and/or develop functional coatings via incorporation the nanoparticles such as TiO 2 nanoparticles have received many attractions, both in industry and in academia.…”
Section: Introductionmentioning
confidence: 99%
“…e presence of those bands confirmed that the organosilane was covalently attached to the additive surface [25]. e new peak at 1216 cm −1 was assigned to Si-C stretching [26]. e chemical structure of the modified UV1 additive was confirmed by 13 C-NMR where the chemical shift at 16.4 ppm, associated with carbon atom that connected to silicon atom (-O-Si-C-) [26], was observed, as shown in Figure 2.…”
Section: Modification Of Uv-absorption Additivesmentioning
confidence: 95%
“…For example, functionalization of metallic nanoparticles, such as titanium dioxide is normally accomplished by using saline coupling agents, (i.e., 1,3,5-triazine and 3-triethoxysilyl propyl isocyanate), which have proven records to increase dispersion of the nanoparticles and to improve the tensile strength 115,116 of the developed nanocomposites.…”
Section: Modification Of Polymeric Nanobiocompositesmentioning
confidence: 99%